Prevalence of Prediabetes and Undiagnosed Diabetes Mellitus among Medical Staff in Tishreen University Hospital (Latakia University Journal -Medical Sciences Series, 2024)
Background :  Pre-diabetes is a real warning sign of developing diabetes. The basic strategy to avoid the transition from pre-diabetes to type 2 diabetes lies in early detection of pre-diabetes to reduce the prevalence of diabetes and its huge economic burdenAim: The aim of this study was to determine the prevalence of pre-diabetes and undiagnosed diabetes among medical staff working at Tishreen University Hospital.Methods: A hospital-based cross-sectional study including 450 participants (230 female and 220 male), age 24 - 65 years surveyed.Type 2 diabetes and pre-diabetes were diagnosed by glycated hemoglobin A1c (HbA1c) levels(diabetes: HbA1c ≥6.5%; pre-diabetes: HbA1c ≥ 5.7% to